The Existence of Sharia Based Regional Regulations In Indonesian Legal System - Irwansyah Irwansyah (Proceeding International Seminar of Islamic Studies, 2019)
Indonesia is a plural state law. This can be seen from the Indonesian national legal system which recognizes and respects the plurality of laws in society. This plural legal system cannot be separated from its historical-empirical experience, that the Indonesian national legal system as it has been known for a long time originates from various legal subsystems, namely the Western legal system, the Customary legal system, and the Islamic legal system. The emergence of a number of shari'a nuanced regional regulations is a very interesting constitutional phenomenon to study considering the content of sharia nuanced regional regulations is the values or teachings of certain religions which in this study are Islamic so that they have been considered to violate the constitutional mandate, violate human rights, discriminatory, and does not reflect tolerance. On the other hand, the birth of shari'ah nuanced regional regulations philosophically-juridically is caused by a paradigm shift that was previously centralistic to decentralized which was marked by the birth of Law Number 22 Year 1999 which was later changed to Law Number 32 Year 2004 and then last changed to Law No 9 of 2015 concerning Regional Government. The decentralization policy contained in the Act then makes people in the regions encouraged to compete in regulating matters relating to their respective regions into a regional regulation including religious affairs. The existence of sharia regulations must be examined based on the national legal system or system, so that its position in the national legal system becomes clear.